Regulation of pga Operon Expression and Biofilm Formation in Actinobacillus pleuropneumoniae by σ(E) and H-NS - Bossé, Janine T. (American Society for Microbiology (ASM), 2010)
Clinical isolates of the porcine pathogen Actinobacillus pleuropneumoniae often form adherent colonies on agar plates due to expression of an operon, pgaABCD, encoding a poly-β-1,6-N-acetyl-d-glucosamine (PGA) extracellular matrix. The adherent colony phenotype, which correlates with the ability to form biofilms on the surfaces of polystyrene plates, is lost following serial passage in broth culture, and repeated passage of the nonadherent variants on solid media does not result in reversion to the adherent colony phenotype. In order to investigate the regulation of PGA expression and biofilm formation in A. pleuropneumoniae, we screened a bank of transposon mutants of the nonadherent serovar 1 strain S4074(T) and identified mutations in two genes, rseA and hns, which resulted in the formation of the adherent colony phenotype. In other bacteria, including the Enterobacteriaceae, H-NS acts as a global gene regulator, and RseA is a negative regulator of the extracytoplasmic stress response sigma factor σ(E). Transcription profiling of A. pleuropneumoniae rseA and hns mutants revealed that both σ(E) and H-NS independently regulate expression of the pga operon. Transcription of the pga operon is initiated from a σ(E) promoter site in the absence of H-NS, and upregulation of σ(E) is sufficient to displace H-NS, allowing transcription to proceed. In A. pleuropneumoniae, H-NS does not act as a global gene regulator but rather specifically regulates biofilm formation via repression of the pga operon. Positive regulation of the pga operon by σ(E) indicates that biofilm formation is part of the extracytoplasmic stress response in A. pleuropneumoniae.